Estudo sobre a aquisição da leitura por crianças: relatos de experiências exitosas - Ferreira, Rosana (2022)
The acquisition of reading represents developmental milestones for children and underpins progress in basic education. The school, through the intervention of literacy teachers, is the institution responsible for stimulating this change in children. Intending to improve the teaching and learning process in schools through new and good practices carried out by literacy teachers, we investigated the process of reading acquisition by children, in a retrospective way. The objective of this research is to analyze successful experiences lived by three teachers graduates of the professional master's course of the Graduate Program in Education at the Federal University of Lavras on the reading acquisition process. This analysis is justified by the possible contributions that the exchange of knowledge can incite for teacher training. Our research had a qualitative approach through the Experience Reports of the invited teachers. Such reports of successful experiences were requested by a digital social network. The identity of each teacher was kept confidential. We asked the teachers to describe what was the successful experience, what was the behavior of the students during learning, what were the teaching methods adopted and difficulties and facilities presented by the students. The results were examined in the light of theories of learning, literacy and literacy, as well as theories of teacher education and teaching practice. We also present the document Base Nacional Comum Curricular BNCC (2018) from the 1st to the 5th year of Portuguese Elementary School in order to understand if the practices contemplate the proposed guidelines. When analyzing the practices reported by the teacher, we understand that such practices, in addition to being effective, are provided for in the BNCC(2018). At the end of this research, we concluded that the acquisition of reading by children depends on literacy associated with literacy. Learning processes in which only literacy or literacy are privileged are not as effective as processes in which literacy and literacy are used together. As an educational product, we prepared an explanatory booklet on the elaboration of Experience Reports, in which we added the reports of our guests.